Investigation of persistant bovine viral diarrhea virus (bvdv) infection at the pregnant cows and their calves bv immunoflourescence and immunperoxidase tests - Orhan Yapkıç; Sibel Yavru (Eurasian Journal of Veterinary Sciences)
Blood samples which were collected with and without EDTA were taken from 62 prenatal pregnant cows, from both cows and precolostral calves at the time of birth and, after approximately 3 months, from postnatal calves which were all present in a private management in this research. Direct immunoflourescence (DIF) and direct immunperoxidase (DPLA) tests were used for virus isolation from leucocyte samples, serum neutralisation test was used to detect antibodies against BVDV. Viral antigen wasn't delected in BVDV from first and second blood samples obtained both all pregnant cows and all calves. By SN testing which was used to detect antibodies against BVDV. while all the pregnant cows were found to be positive after both sampling, 7 precolostral calves were positive and 55 precolostral calves were negative all the calves, from which the second sampling was carried out approximately during 3 months after birth, were detected as positive. SN50 titers of the pregnant cows from which sera samples were collected before birth were noted between 1/7,5 and 1/160≤ However, SN50 titers of sera taken from cows just after giving birth were detected between 1/7,5 and 1/160≤ The sera samplss obtained from 7 precolostral - seropositive calves immediately following birth, SN50 titers were lound to be between 1/20 and1/120. The samples taken from calves within 3 months after birth SN50 tilers were detected between1/5 and 1/160.